Systematic review and meta‐analysis of the anatomical variants of the left colic artery. (21st November 2019) - Cirocchi, R.; Randolph, J.; Cheruiyot, I.; Davies, J. R.; Wheeler, J.; Lancia, M.; Gioia, S.; Carlini, L.; di Saverio, S.; Henry, B. M.
Abstract: Aim: To provide a comprehensive evidence‐based assessment of the anatomical variations of the left colic artery (LCA). Method: A thorough systematic search of the literature up until 1 April 2019 was conducted on the electronic databases PubMed, SCOPUS and Web of Science (WOS) to identify studies eligible for inclusion. Data were extracted and pooled into a meta‐analysis using the Metafor package in R. The primary outcomes of interest were the absence of the LCA and the anatomical variants of its origin. The secondary outcomes were the distance (mean ± SD) between the origin of the inferior mesenteric artery (OIMA) and the origin of the left colic artery (OLCA). Results: A total of 19 studies ( n = 2040 patients) were included. The pooled prevalence estimate (PPE) of LCA absence was 1.2% (95% CI 0.0–3.6%). Across participants with either a Type I or Type II LCA, the PPE of a Type I LCA was 49.0% (95% CI 40.2–57.8%). The PPE of a Type II LCA was therefore 51.0%. The pooled mean distance from the OIMA to the OLCA was 40.41 mm (95 CI% 38.69–42.12 mm). The pooled mean length of a Type I LCA was 39.12 mm (95% CI 36.70–41.53 mm) while the pooled mean length of a Type IIa and Type IIb LCA was 41.43 mm (95% CI 36.90–43.27 mm) and 39.64 mm (95% CI 37.68–41.59 mm), respectively. Conclusion: Although the absence of the LCA is a rare occurrence (PPE 1.2%), it may be associated with an important risk of anastomotic leakage as a result of insufficient vascularization of the proximal colonic conduit. It is also necessary to distinguish variants I and II of Latarjet, the frequency of which is identical, with division of the LCA being technically more straightforward in variant I of Latarjet. Surgeons should be aware that technical difficulties are likely to be more common with variant II of Latarjet, as LCA ligation may be more difficult due to its close proximity to the inferior mesenteric vein (IMV).